Physical characteristics and physiological attributes of adolescent volleyball players - a review - Lidor, R.; Ziv, G. (Pediatric Exercise Science, 2010)
The purpose of this article was to review a series of studies (n = 31) on physical characteristics, physiological attributes, and volleyball skills of female and male adolescent volleyball players. Among the main findings were (a) that male national players were taller and heavier than state and novice players, while female national players showed lower body fat values compared with state and novice players, and (b) vertical jump values were higher in starters versus nonstarters. Among the methodological concerns based on the reviewed studies were the lack of information on maturational age and lack of longitudinal studies. It was recommended that a careful selection of physiological tests should be made when assessing the abilities of adolescent volleyball players.